Paradox at Work: Unraveling Stress and Turnover in Healthcare: Evidence in Indonesian Hospitals - Albert Diaz Pratama; Innocentius Bernarto (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This study aims to analyze the influence of leadership, job demands, and job resources on work stress and turnover intention of hospital staff, with work stress as a mediating variable. The study was conducted on medical and non-medical staff at three hospitals in Indonesia using a quantitative approach. A sample of 200 respondents was selected through purposive sampling with the criteria of a minimum of six months of service and direct involvement in hospital operations. Data were collected through a structured questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that leadership, job demands, and job resources significantly influenced work stress. Leadership and job demands also positively influenced turnover intention. In addition, work stress was shown to mediate the influence of leadership, job demands, and job resources on turnover intention. This study concluded that effective leadership management, job demand management, and job resource optimization play a significant role in reducing work stress and turnover intention of hospital staff. These findings provide practical implications for hospital management in improving workforce well-being and retention.